Functional activity of HERV-K-T47D-related long terminal repeats - Baust, Corinna; Seifarth, Wolfgang; Schön, Ulrike; Hehlmann, Rüdiger; Leib-Mösch, Christine (Virology, 2001)
The human genome contains a family of endogenous retroviruses, HERV-K(HML-4), that comprises the full-length provirus HERV-K-T47D, five related elements, and hundreds of solitary long terminal repeats (LTRs). We here show that HERV-K-T47D-related LTRs are dispersed over all human chromosomes and have arisen after the divergence of Old and New World monkeys. By screening a cDNA library derived from the human mammary carcinoma cell line T47D with a HERV-K-T47D LTR probe, we isolated several clones containing LTR/cellular gene chimeras and assessed the transcriptional activity of these LTRs in transient transfection experiments. All LTRs were able to drive the expression of a reporter gene, thereby displaying distinct activities in different cell lines. We found that sequences located downstream of the LTR-U3 region modulate the level of gene expression. Based on the impact of the R region we distinguished between three different LTR types; the activity of type I LTRs was enhanced in the presence of the LTR-R region in all cell lines tested, whereas a type II LTR was downregulated. Type III LTRs are characterized by lacking or having a varying influence of the R region that was dependent on the cell line used. Finally, our results attribute to LTR-U5-gag sequences a role in determining LTR activity.
Elektronische Reproduktion der Druckausgabe
Gesehen am 18.05.2022